The Analysis Of Type Of Code Switching Used By Students On English Class - Anis Mailing; Rani Herning Puspita (Departement of Mathematics Education, 2022)
Code switching is common activity that occurs in society with many different languages. It is not only happen in daily conversation between two people but also occurs in English class in Indonesia. The activities in English class between teacher and students contain a lot of code switching. The purpose of this study was to analyze the level and of code switching used by students in delivering utterances during the activity in English class. The research used recording and note-taking to collect the data. The subjects in this study were 6 students in class XI accounting at SMK N 4 Samarinda. The results of the research was found that the students used tag code switching as many as 50%, intra sentential code switching 15% and inter sentential code switching 35%